Pengembangan Model Standar Isi Mata Pelajaran PAI pada Jenjang Sekolah - Ended Hamzah Suaidi; Siti Hilmah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The development of a content standard model referred to in this research study is developing content standards for PAI subjects whose material content is still general in nature and still needs to be specified so that it can be further developed and compiled into teaching materials and/or textbooks for PAI subjects. What is meant by PAI subject content standards at the school level here refers to the Minister of Education and Culture, Research and Technology Regulation No. 8 of 2024 (Attachment Copy). These content standards can be used as a reference for the development and preparation of teaching materials and/or textbooks for PAI subjects at the elementary, middle school, high school/vocational school or equivalent levels. The aim of the study here is to develop a standard model for the content of PAI subjects at the school level is to develop a standard model for the content of Islamic Religious Education (PAI) subjects in elementary, middle school, high school/vocational school or equivalent with the target; First; Develop and formulate learning objectives, learning outcomes, and formulate competencies for PAI subject graduates, Second; develop content standard models into teaching materials and/or textbooks for PAI subjects and develop PAI material components. The approach used in this study is the development of a standard model of PAI subject content at the school level with a descriptive narrative explanation type. Data collection in this research was carried out by compiling the standard content of PAI subject content for elementary, middle school, high school/vocational school or equivalent levels, the content of which is still general in nature, so it is necessary to develop and prepare more detailed and in-depth material into teaching materials and/or textbooks for PAI subjects. The form of developing a content standard model is through assessing and reviewing PAI material into teaching materials and/or textbooks for PAI subjects that can be used at the school level. The results of research studies on the development of standard content models here include developing and compiling the content of teaching materials and/or textbooks for PAI subjects for elementary, middle school, high school/vocational school or equivalent levels, which need to include the content of learning objectives, material descriptions/scripts, and assessment/evaluation tools, as well as learning outcomes and graduate competencies. PAI subject content standards at the school level can be developed and compiled into PAI teaching materials and/or textbooks which include material components that include discussion of Aqidah Akhlak, Al-Quran-Hadith, Jurisprudence/Practice of Worship, History of Islamic Culture, and an introduction to the basics of Arabic and reading and writing the Al-Quran. Developers, compilers and teachers of PAI subjects can further develop content standards into teaching materials and/or textbooks for PAI subjects at school level. In this research study, the content of teaching materials for elementary, middle school, high school/vocational school or equivalent levels has been described which can be used as an example of developing a standard model of content at the school level.